2012
DOI: 10.1007/s15010-012-0316-8
|View full text |Cite
|
Sign up to set email alerts
|

Previous outpatient antibiotic use in patients admitted to hospital for COPD exacerbations: room for improvement

Abstract: This study demonstrates a low rate of previous outpatient treatment and antibiotic use among patients with a COPD exacerbation requiring hospital admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Hospitalizations have important social and economic implications as well (18). By the way, a low rate of previous antibiotic use among patients with a COPD exacerbation requiring hospital admission has been reported in the literature (19); therefore, our study population seems once again of interesting originality.…”
Section: Discussionmentioning
confidence: 85%
“…Hospitalizations have important social and economic implications as well (18). By the way, a low rate of previous antibiotic use among patients with a COPD exacerbation requiring hospital admission has been reported in the literature (19); therefore, our study population seems once again of interesting originality.…”
Section: Discussionmentioning
confidence: 85%
“…In the past, long-term administration of antibiotics was used to treat acute exacerbations of COPD, but metaanalyses of the studies of antibiotic administration showed no significant benefit (2). A multicenter, crosssectional, observational study was conducted in 30 Spanish hospitals among COPD patients aged > 40 years who were hospitalized for an acute exacerbation showed that antibiotic use was significantly associated with yellow or green-yellow sputum prior to the exacerbation, a higher number of exacerbations in the previous year, more visits to emergency departments, and bronchiectasis (3). Because of these problems with antibiotic treatment, more and more traditional Chinese physicians are focusing on exploring the therapeutic effect of Chinese herbal medicine in COPD.…”
Section: Introductionmentioning
confidence: 99%